2005
DOI: 10.1167/iovs.04-0956
|View full text |Cite
|
Sign up to set email alerts
|

In a Matter of Minutes, the Eye Can Know Which Way to Grow

Abstract: The eyes of chicks require only a brief period of lens wear to initiate compensation in the appropriate direction. Because the refractive status changes little during the period of lens wear, the authors conclude that eyes can rapidly determine the sign of the imposed blur without resorting to a trial-and-error method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
138
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(154 citation statements)
references
References 22 publications
(27 reference statements)
13
138
0
3
Order By: Relevance
“…[25][26][27] The reduced retinal activity (analogous to visual deprivation) could become an error signal for eye growth processes. In chicks, 2 to 3 minutes of exposure to defocus is sufficient to induce changes in eye growth, 28,29 so reading for more than an hour (which is not uncommon, with a previous study on Singaporean children reporting that some children read for up to 3 hours before bedtime 30 ) could be very detrimental.…”
Section: Myopes Versus Emmetropesmentioning
confidence: 99%
“…[25][26][27] The reduced retinal activity (analogous to visual deprivation) could become an error signal for eye growth processes. In chicks, 2 to 3 minutes of exposure to defocus is sufficient to induce changes in eye growth, 28,29 so reading for more than an hour (which is not uncommon, with a previous study on Singaporean children reporting that some children read for up to 3 hours before bedtime 30 ) could be very detrimental.…”
Section: Myopes Versus Emmetropesmentioning
confidence: 99%
“…Thickening and thinning of choroidal thickness indicate that the defocus signals have to be recognised by the retina to modulate the rate of axial elongation. Recognition of the blur takes only two minutes (Zhu et al, 2005). Dopamine reduction and myopia inhibitory effects of dopamine agonist during the development of FDM were firstly reported by Stone and the colleagues (1989a).…”
Section: Myopia In Animalsmentioning
confidence: 93%
“…A number of theories have been put forward over the last two decades that link choroidal expansion and contraction to alterations in blood flow, fluid levels or the tone of choroidal nonvascular smooth muscles (Junghans et al, 1999;Pendrak et al, 2000;Kee et al, 2001;Zhu et al, 2005;Rada and Palmer, 2007;Nickla, 2007;Nickla and Wallman, 2010a). Histological studies and experiments using stimulation of the autonomic system have revealed a rich autonomic vasoactive nerve supply to the choroid (Ehinger, 1966;Ruskell, 1971;Stjernschantz and Bill, 1980, Nilsson et al, 1985, Stone, 1986.…”
Section: The Autonomic Control Of Choroidal Thickness Changesmentioning
confidence: 99%
“…It has been assumed that signal transduction starts in the retina and that the retinal pigment epithelium is likely to play a key role in relaying signals between the retina, the choroid and the sclera. The choroid responds to blur with thickness changes that are rapid (minutes to hours) (Zhu et al, 2005), and typically precede axial length changes, due to scleral remodelling, which is a longerterm process (McBrien, 2013). The majority of work that has contributed to the current understanding of the influence of retinal image quality on choroidal thickness changes has come from animal studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation